Investigating language isolates: typological and diachronic perspectives - Salaberri, Iker; Krajewska, Dorota; Reguero, Urtzi; Zuloaga, Eneko; Duhalde, Maitena collaborator; Uribe-Etxebarria, Oxel collaborator; Monforte, Sergio collaborator; Santazilia, Ekaitz collaborator; Ariztimuño, Borja collaborator; Ulibarri, Koldo collaborator (Zenodo, 2020)
Dear colleagues, we would like to draw your attention to the call for papers for the workshop "Investigating language isolates: typological and diachronic and perspectives", which (if accepted) will take place during the 54th Annual Meeting of the Societas Linguistica Europaea in Athens, August 31 to September 3, 2021. With best wishes, Iker Salaberri, Dorota Krajewska, Urtzi Reguero and Eneko Zuloaga (with the collaboration of Maitena Duhalde, Oxel Uribe-Etxebarria, Sergio Monforte & Ekaitz Santazilia) *** Call for papers Preliminary abstracts of no more than 300 words (excluding references) in .doc, .docx, .odt or .pdf format should be sent before November 1, 2020, to ikersalaberri@gmail.com. Any questions or suggestions regarding the workshop are very welcome as well. Investigating language isolates: typological and diachronic perspectives Iker Salaberri, Dorota Krajewska, Urtzi Reguero & Eneko Zuloaga (with the collaboration of Maitena Duhalde, Oxel Uribe-Etxebarria, Sergio Monforte & Ekaitz Santazilia) (Université Sorbonne Nouvelle - Paris 3 & University of the Basque Country & Public University of Navarre) Keywords : language isolates; typology; language history; comparative linguistics; language documentation and filiation Recent years have witnessed advances in the study of language isolates (lis) (Campbell (ed.) 2017). However, and despite the fact that lis represent nearly 40% of the world’s language families (Campbell 2017a: xi), they are still underrepresented in part of typological and comparative literature: see, for example, the objections by Miestamo et al. (2016) concerning sampling procedures in Voegelin & Voegelin (1977) and Bybee et al. (1994). In addition, little is known about the histories of most of these languages (Hombert & Philippson 2009). This state of affairs is due to many reasons: in line with current world-wide tendencies, many lis are becoming extinct even before they get the chance to be documented (Harrison 2007), and the lack of comprehensive information hinders a correct genetic affiliation of these languages, which often precludes their being treated as isolates (Blench 2017: 162). The lack of research on lis from specific perspectives, for instance diachronic-historical linguistics, is also influenced by preconceived ideas including the view that isolates do not have a history: Meillet (1925: 11-12), for example, claims that “if a language is isolate, it is deprived of history”. As a result of this data situation, it is unclear whether lis are, from a typological and diachronic perspective, similar or different in comparison to non-isolates: whereas some authors contend that “language isolates are not very different from language families composed of multiple members” (Campbell 2017b: 1), other recent studies point in the opposite direction. The latter signal an overrepresentation —or at least presence— of typologically unusual features in isolates, such as the contrast between plain and post-aspirate nasals in Nasa Yuwe (Jung 2000: 141-142), verbal allocutivity in Basque, Nambikwara and Pumé (Antonov 2015: 80-81), the lack of an unambiguous standard negative system in Kusunda (Donohue et al. 2014) and a twenty-four-way system of numeral series according to the type of counted objects in Nivkh (Georg 2017: 148-149). Far less is known regarding the diachronic facet of lis, despite the fact that a few languages such as Basque, Elamite, Mapudungun and Sumerian, among others, have sufficient textual evidence stretching over relatively long periods of time so as to allow for comprehensive historical and philological research (Hayes 1990, Khačikjan 1998, Zúñiga 2006, Campbell 2011, Ulibarri 2013). This workshop is meant to delve deeper into the questions concerning the typological features and histories of lis from different theoretical perspectives. It is also interested in exploring and discussing recent findings with respect to the documentation and filiation of endangered and poorly described lis. We welcome contributions that address, among others, the following topics: - what similarities and differences are there concerning the typological features of language isolates vs. non-isolates? - how can we advance our knowledge of the history of language isolates? - what similarities and differences are there concerning the historical changes of language isolates vs. non-isolates? - how does linguistic contact affect language isolates? - how much documentation, and of what kind, is necessary to determine the isolate status of languages? Contributions that address these questions could be oriented in the following manner: - comparative typological and/or historical studies on isolates and non- isolates; - corpus studies on the historical development of language isolates; - studies which attempt internal reconstruction of language isolates; - studies on the documentation of little-described or previously undescribed language isolates; - studies that discuss attempts to establish the genetic filiation of language isolates and/or unclassified languages. References Antonov, Anton. 2015. Verbal allocutivity in a crosslinguistic perspective. Linguistic Typology 19(1). 55-85. Blench, Roger. 2017. African language isolates. In Lyle Campbell (ed.), Language isolates , 162-192. London/New York: Routledge. Bybee, Joan, Revere Perkins & William Pagliuca. 1994. The evolution of grammar: Tense, aspect and modality in the languages of the world . Chicago: Chicago University Press. Campbell, Lyle R. 2011. La investigación histórica de las lenguas aisladas, o ¿es raro el vasco? In Joseba A. Lakarra, Joaquín Gorrochategui & Blanca Urgell (eds.), 2 nd Conference of the Luis Michelena Chair , 23-40. Vitoria-Gasteiz: University of the Basque Country Editorial Service. Campbell, Lyle R. (ed.). 2017. Language isolates . London/New York: Routledge. Campbell, Lyle R. 2017a. Introduction. In Lyle Campbell (ed.), Language isolates , xi-xiv. London/New York: Routledge. Campbell, Lyle R. 2017b. Language isolates and their history. In Lyle Campbell (ed.), Language isolates , 1-18. London/New York: Routledge. Donohue, Mark, Bhojraj Gautam & Madhav Pokharel. 2014. Negation and nominalization in Kusunda. Language 90(3). 737-745. Georg, Stefan. 2017. Other isolated languages of Asia. In Lyle Campbell (ed.), Language isolates , 139-161. London/New York: Routledge. Harrison, K. David. 2007. When languages die: The extinction of the world’s languages and the erosion of human knowledge . Oxford: Oxford University Press. Hayes, John L. 1990. A manual of Sumerian grammar and texts (2nd edition). Malibu: Undena Publications. Hombert, Jean-Marie & Gérard Philippson. 2009. The linguistic importance of language isolates: The African case. In Peter K. Austin, Oliver Bond, Monik Charette, David Nathan & Peter Sells (eds.), Proceedings of Conference on Language Documentation and Linguistic Theory 2. London: School of Oriental and African Studies. Jung, Ingrid. 2000. El páez: Breve descripción. In María S. González de Pérez & María L. Rodríguez de Montes (eds.), Lenguas indígenas de Colombia: Una visión descriptiva , 139-154. Santafé de Bogotá: Instituto Caro y Cuervo. Khačikjan, Margaret. 1998. The Elamite language . Rome: Consiglio nazionale delle ricerche. Meillet, André. 1925. La méthode comparative en linguistique historique . Oslo: H. Aschehoug & Co. (W. Nygaard) Miestamo, Matti, Dik Bakker & Antti Arppe. 2016. Sampling for variety. Linguistic Typology 20(2). 233-296. Ulibarri, Koldo. 2013. External history: Sources for historical research. In Mikel Martínez-Areta (ed.), Basque and Proto-Basque: Language-internal and typological approaches to linguistic reconstruction , 89-117. Frankfurt am Main: Peter Lang. Voegelin, Charles F. & Florence M. Voegelin. 1977. Classification and index of the world’s languages . New York: Elsevier. Zúñiga, Fernando. 2006. Mapudungun: El habla mapuche . Santiago de Chile: Centro de Estudios Públicos.